Penerapan Metode Profile Matching Untuk Pengadaan Koleksi di Perpustakaan Universitas Metamedia Padang - Raisha Salsabila Putri; Marlini Marlini (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to describe how librarians determine library collections and describe the application of the Profile Matching method in procuring collections at the Metamedia Padang University Library. This research is a type of quantitative research with descriptive methods. Data was obtained through distributing questionnaires at the Metamedia Padang University Library. The population in this research were all Metamedia Padang University students from the entry year 2020 to 2022, totaling 1036 people. The sampling technique used cluster sampling with a total sample of 91 respondents. The data collection technique was carried out by distributing questionnaires to the research sample.In this research, the data analysis technique uses quantitative descriptive statistics. Based on the results of data analysis, this research showed that the application of the profile matching method to determine book procurement at the Metamedia Padang University Library and its suitability for student information needs with four indicators obtained an average score of 3.67. First, on the latest information needs indicator, an average score of 4.39 was obtained, which is on a good interval scale. Second, on the indicator of routine information needs, an average score of 4.33 was obtained, which is on a good interval scale. Third, on the indicator of need for in-depth information, an average score of 3.90 was obtained, which is on a good interval scale. Fourth, on the information needs indicator at a glance, an average score of 2.04 was obtained in the poor category. Overall, the results of this research can be concluded that the application of the profile matching method to determine book procurement at the Metamedia Padang University Library is good.